2006
DOI: 10.2215/cjn.01891105
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postdialysis Blood Pressures Are Imprecise Estimates of Interdialytic Ambulatory Blood Pressure

Abstract: H ypertension is perhaps one of the most pervasive problems of patients with ESRD. Although current guidelines that focus on cardiovascular disease in dialysis patients call for hypertension control as a top priority, the vast majority of patients who are on hemodialysis are hypertensive and control rates are poor (1). For practical reasons, BP assessment and antihypertensive treatment in patients with ESRD is performed on the basis of measurements that are made either immediately before or after dialysis. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
157
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 40 publications
6
157
2
11
Order By: Relevance
“…Although measurement of BP before starting and immediately at the end of dialysis is highly variable, dependent on fluid volume status and the hemodynamic effects of dialysis, it remains the clinical standard. Twenty-four-hour ambulatory BP monitoring studies have confirmed these associations (24), but this method is not universally available, is time-consuming, and is uncomfortable for dialysis patients.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadmentioning
confidence: 99%
“…Although measurement of BP before starting and immediately at the end of dialysis is highly variable, dependent on fluid volume status and the hemodynamic effects of dialysis, it remains the clinical standard. Twenty-four-hour ambulatory BP monitoring studies have confirmed these associations (24), but this method is not universally available, is time-consuming, and is uncomfortable for dialysis patients.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadmentioning
confidence: 99%
“…However, predialysis and postdialysis BP measurements are generally inaccurate estimates of ambulatory BP measurements (10). In the dialysis unit, BP measurements are obtained every 30 min during dialysis, primarily to ensure the hemodynamic stability of patients during treatment.…”
mentioning
confidence: 99%
“…Wide limits of agreement and heterogeneity between studies limit generalizability of conclusions among these patients. 2 In particular, the escalating disagreement with increasing stages of hypertension is a particular concern in the study by Liu and colleagues. 1 All too often, farreaching conclusions are made about BP control for the rest of the week based on these readings.…”
mentioning
confidence: 99%
“…3 It is unfortunate that nephrologists in current North American practice are rarely present on site during outpatient renal dialysis, unlike their European or Japanese counterparts. The relative lack of "presence" of a nephrologist, along with limited reimbursement and scarcity of trained nursing staff may have contributed to the slow implementation of ABPM among dialysis patients in North America, despite its proven efficacy 2,4 and excellent acceptance of the procedure. 5 One interesting but perhaps less well-studied aspect of dialysis-derived BP readings is the relative correlation of predialysis or postdialysis values, independent of each other, with results obtained by ABPM.…”
mentioning
confidence: 99%